Designing heterogeneous hierarchical material systems: a holistic approach to structural and materials design. (June 2019) - Ryan, Emily; Pollard, Zoe A.; Ha, Quang-Thinh; Roshandelpoor, Athar; Vakili, Pirooz; Goldfarb, Jillian L.
Abstract: Abstract : Many materials systems comprise complex structures where multiple materials are integrated to achieve a desired performance. Often in these systems, it is a combination of both the materials and their structure that dictate performance. Here the authors layout an integrated computational–statistical–experimental methodology for hierarchical materials systems that takes a holistic design approach to both the material and structure. The authors used computational modeling of the physical system combined with statistical design of experiments to explore an activated carbon adsorption bed. The large parameter space makes experimental optimization impractical. Instead, a computational–statistical approach is coupled with physical experiments to validate the optimization results.